Inovasi Teknik Origami Jepang pada Busana Avant-Garde - Rina Puji Lestari; Mien Zyahratil Umami (Garina, 2025)
The continuously evolving fashion industry encourages designers to innovate, one such way being the adaptation of Japanese origami techniques into avant-garde fashion design. This research explores the application of origami butterfly forms in garments using a Research and Development (R&D) methodology. This methodology involves stages such as (1) potential problems, (2) data collection (literature review, observation, documentation), (3) product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision, (8) wear trial, (9) product revision, and (10) mass production.The objectives of this study are to understand the application of innovative Japanese origami techniques in avant-garde fashion and to detail the garment creation process utilizing these techniques. In this research, the author focuses on the origami form as the central point. The findings indicate that origami techniques can produce unique and strong visual structures. A technical tip for creating these garments is to use a larger stitch size (7 stitches per inch) when sewing synthetic leather to prevent material damage. Expert validation suggests that this design has the potential to be developed as a contemporary fashion innovation, blending traditional values with modernity. This research is expected to serve as a reference for designers and academics interested in incorporating traditional techniques into modern fashion works.